Monogenean Parasites of White Bream (Blicca bjoerkna Linnaeus, 1758) in Lake Sapanca, Turkey - (:unkn) unknown (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2012)
A survey was made of monogenean parasites on 123 Blicca bjoerkna caught from Lake Sapanca between December 2007 and November 2008. Nine monogenean species were found: Dactylogyrus sphyrna Linstow, 1878, D. falcatus (Wedl, 1857), D. difformoides Glaser and Gussev, 1971, D. wunderi Bykhovskii, 1931, D. cornu Linstow, 1878, D. cornoides Glaser and Gussev, 1971, D. distinguendus Nybelin, 1937, Gyrodactylus sp. and Paradiplozoon sp. Of these monogeneans, D. sphyrna, D. cornu and D. cornoides were numerically dominant in all the host specimens examined, each having a prevalence of 100% in some spring and summer months. These were followed in numerical dominance and prevalence by D. distinguendus and Gyrodactylus sp. The other parasite species were found infrequently, four or five species groups predominated particularly during the spring and summer months. D. wunderi and D. falcatus, found only in June and July on just three host specimens, are new records for Turkey.
Keywords: Monogenean; Parasite; White bream; Lake Sapanca; PLATYHELMINTH PARASITES; HOST-SPECIFICITY